2017
DOI: 10.3892/ol.2017.6619
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO blood groups with von Willebrand factor, factor VIII and ADAMTS-13 in patients with lung cancer

Abstract: Abstract. Coagulative and fibrinolytic disorders appear to be associated with the development of lung cancer. The aim of the present study was to determine plasma levels of von Willebrand factor (VWF) and a disintegrin and metalloproteinase with a thrombospondin type 1 motif 13 (ADAMTS-13), and factor VIII (FVIII) activity, in association with O and non-O blood groups in patients with lung cancer. Plasma levels of VWF and ADAMTS-13, and FVIII activity were measured in 115 patients with lung cancer and 98 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
1
21
0
3
Order By: Relevance
“…24 Our results are also supported by previously published studies in which the non-O blood group members have been shown to have greater concentrations of Von Will brand clotting factors. 25,26 Since high cholesterol and high concentration of Von will brand factors in blood type A population (a non-O blood group) puts a person at higher risk of stroke and it is reasonable to assume that the patients of A blood group in Saudi adult population are at higher risk of stroke as suggested by our results in this study. In the current study as expected, we also found a high prevalence of smoking however we found high prevalence of smoking not only in control subjects but also in male stroke patients (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 78%
“…24 Our results are also supported by previously published studies in which the non-O blood group members have been shown to have greater concentrations of Von Will brand clotting factors. 25,26 Since high cholesterol and high concentration of Von will brand factors in blood type A population (a non-O blood group) puts a person at higher risk of stroke and it is reasonable to assume that the patients of A blood group in Saudi adult population are at higher risk of stroke as suggested by our results in this study. In the current study as expected, we also found a high prevalence of smoking however we found high prevalence of smoking not only in control subjects but also in male stroke patients (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 78%
“…45 Furthermore universal donor type O required for early transfusion of WB, has lower factor VIII activities compared to other blood groups. 46 In clinical practice these small differences in coagulation factor activity will probably have minimal impact on the clinical outcome of patients with major hemorrhage. The reduction of plasma in PAS stored platelets may have a significant effect compared to platelets stored in plasma in this patient category, though this has yet to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Several plausible mechanisms could account for the association between ABO blood group antigens and cancer development and progression (3,(8)(9)(10). Glycosyltransferase is encoded by the ABO gene located on chromosome 9q34.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the enzymatic activity of ABO glycosyltransferase play an important role in the activation of adhesion molecules, intracellular signaling, and determination of the level of von Willebrand factor (VWF), thereby affecting tumor growth and spread (3,(8)(9)(10). VWF is a multimeric glycoprotein, which is synthesized in endothelial cells, and is one of several platelet adhesion ligands that could potentially modulate cancer development and metastasis (3,8). The VWF antigen level in adults is, on average, about 25% to 30% lower in blood group O individuals than in non-O individuals (26,27).…”
Section: Discussionmentioning
confidence: 99%